St. Miguel Febres Cordero research award - De La Salle University, Manila (Animo Repository, 2003)
DLSU-Manila granted four faculty members the St. Miguel Febres Cordero Research Award during the 2003 Annual Faculty Recognition Day. This year's recipients of the award are Dr. Gloria Chavez (CBE), Dr. Antonio Contreras (CLA), Dr. Andres Oreta (COE) and Dr. Allan Bernardo (VP-AR).